Graham Roberts Study protocol: first 'trials within cohort study' for bladder cancer. Issue 9 (26th September 2019) - Wylie, Harriet; Cahill, Fidelma; Santaolalla, Aida; Moss, Charlotte Louise; Enting, Deborah; Amery, Suzanne; Chatterton, Kathryn; Khan, Muhammad Shamim; Bryan, Richard T; Gillett, Cheryl; Josephs, Debra; Chowdhury, Simon; et al.
Abstract : Introduction: Given the need for more bladder cancer research and the recently observed advantages of introducing the trials within cohort (TwiCs) design, the set-up of the Graham Roberts Study (Roberts Study) will provide valuable infrastructure to answer a wide variety of research questions of a clinical, mechanistic, as well as supportive care nature in the area of bladder cancer. Methods: Using the TwiCs design, we will recruit patients aged 18 or older who are willing and able to provide signed informed consent and have a diagnosis of new or recurrent bladder cancer into this prospective cohort study. All patients must have a basic understanding of the English language. The following questionnaires will be collected at baseline and every 12 months subsequently: Functional Assessment of Chronic Illness Therapy for Bladder Cancer, the Functional Assessment of Chronic Illness Therapy-Fatigue, the Patient Heath Questionnaire-9, the standardised instrument for a generic health status (EQ-5D-5L), a Short Questionnaire to Assess Health-Enhancing Physical Activity and the Hertfordshire Short Questionnaire to Assess Diet Quality. Ethics and dissemination: Due to the nature of this study, we obtained full ethical clearance from the London—Fulham Research Ethics Committee (17/LO1975). All participants must provide full informed consent before recruitment onto the study. The results of this study will be published in peer-reviewed journals and data collected as part of the study will be made available to potential collaborators on an application basis.